Herpes Simplex Virus Type 1 and Type 2 Infection Increases Atherosclerosis Risk: Evidence Based on a Meta-Analysis. (19th April 2016) - Wu, Yu peng; Sun, Dan dan; Wang, Yun; Liu, Wen; Yang, Jun
Abstract : Objective. The aim of our study was to evaluate the relation of herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) infection with the risk of atherosclerosis (AS). Methods. A systematic literature search was performed through three electronic databases. The pooled odds ratio (OR) and corresponding 95% confidence interval (CI) were used to assess the effect of HSV-1 and HSV-2 infection on AS risk. Results. 17 studies were available for meta-analysis of HSV-1 infection and AS risk and seven studies for meta-analysis of HSV-2 infection and AS risk. Subjects exposed to HSV-1 infection exhibited an increased risk of AS (OR = 1.77; 95% CI: 1.40–2.23; P < 0.001 ). And consistent elevated AS risks for HSV-1 positive subjects were found in all subgroup analysis of disease type, region, male proportion, and age. HSV-2 positive subjects demonstrated significantly increased AS risk (OR = 1.37; 95% CI: 1.13–1.67; P < 0.005 ). In subgroup analysis, elevated AS risks were only observed in myocardial ischemia group, male proportion >60% group, and age ≤60-year-old group. Conclusion. Our meta-analysis indicated that HSV-1 and HSV-2 infection could increase the risk of contracting AS.